Enterococci in the oral cavity of periodontitis patients from different urban socioeconomic groups - Bhardwaj, Sonia Bhonchal (Dent Res J (Isfahan), 2020)
BACKGROUND: Enterococci are the transient constituents of the oral microbiome and have been now increasingly related to oral and systemic diseases. They have now become the most notable nosocomial pathogens and also been linked to etiology of periodontitis. This study evaluates the prevalence of Enterococci in the chronic periodontitis and healthy Indian cohort in different urban socioeconomic groups. MATERIALS AND METHODS: In this retrospective study, individuals in the age range of 18.75 years were included. Seventy individuals had mild-to-moderate periodontitis and 30 healthy persons were taken as controls. A questionnaire was administered. Paper point samples of gingival crevicular fluid were obtained, pooled, and sent to microbiology laboratory in a transport media. Forty-six isolates were identified as enterococci for statical analyzes Pearson’s Chi-square test used and. P < 0.001 was considered to be significant. RESULTS: The prevalence of enterococci was seen mostly in the individuals from lower socioeconomic class, having poor oral hygiene, and smokers. This was significantly different from those of upper class (P < 0.001). The predominant species isolated was Enterococcus faecalis. CONCLUSION: Enterococci particularly E. faecalis followed by Enterococcus faecium could play a crucial role in the severity or progression of periodontitis particularly in a favorable oral environment.